Influence Background Behind Education, Utilization System Information and Internal Control of Quality Report Finance (Study Case at Cleaning and Parks Department of Pemerintah Kota Medan) - Dinda Rizki Sakinah Kasim; Oktarini Khamilah Siregar (Universitas Kristen Indonesia Toraja, 2022)
This research aims to empirically test the influence of educational background, use of information systems, and internal control on the quality of financial reports at the Medan City Cleaning and Parks Service. The data used in this research uses primary data in the form of distributing questionnaires with 30 employees as respondents. Data obtained was processed using statistical formulas, namely by using multiple regression analysis processed with the SPSS Version 23 program. Results Research shows that educational background variables, use of information systems, and internal control positively affect the quality of the financial reports of the Medan City Cleaning and Parks Department.